Online Learning Review of English Language Teaching in SMK N 8 Purworejo - Indiana Surya Pratiwi Indi; Semi Sukarni; Abdul Ngafif (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2021)
This research aims to find out students’ perception on online learning of English subject during Covid-19 pandemic at SMK N 8 Purworejo. The researchers collected the data through a questionnaire and interviews. There were 72 students of 12th grade at SMK N 8 Purworejo participated in this research. This research used mixed method approach combined qualitative and quantitative approaches. Descriptive analysis was used to analyze data from questionnaire and thematic analysis was used to analyze data from interview. The result of this research shows that 12th grade students of SMK N 8 Purworejo have “medium” perception toward the implementation of online learning during Covid-19 pandemic. The mean score of the questionnaire was 3.21 that lays on the range between 2.60 – 3.39 which can be interpreted in the “Medium” category. Besides, there were several difficulties faced by students and teachers. This difficulties, such as the bad signal or internet connection, the lack of variation on online learning methods and media platform in online learning, and the lack of interaction that occurs during online learning between students and teachers, and students with students. These difficulties make online learning becomes less effective.